2015
DOI: 10.1109/jlt.2015.2493202
|View full text |Cite
|
Sign up to set email alerts
|

Low-Complexity Tracking of Laser and Nonlinear Phase Noise in WDM Optical Fiber Systems

Abstract: Abstract-In this paper the wavelength division multiplexed (WDM) fiber optic channel is considered. It is shown that for ideal distributed Raman amplification (IDRA), the Wiener process model is suitable for the non-linear phase noise due to cross phase modulation from neighboring channels. Based on this model, a phase noise tracking algorithm is presented. We approximate the distribution of the phase noise at each time instant by a mixture of Tikhonov distributions, and derive a closed form expression for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…We note that the BPS and the TMM receiver take advantage of the QPSK pilot symbols: the former by using the actual transmitted symbol when estimating the cost function in Eq. (3), and the latter by exploiting the fact that the prior distribution p(x k ) = 1 for the true symbol and p(x k ) = 0 for all other symbols at the pilot instances (details are given in [13]). …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We note that the BPS and the TMM receiver take advantage of the QPSK pilot symbols: the former by using the actual transmitted symbol when estimating the cost function in Eq. (3), and the latter by exploiting the fact that the prior distribution p(x k ) = 1 for the true symbol and p(x k ) = 0 for all other symbols at the pilot instances (details are given in [13]). …”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that this model can also be used with reasonable accuracy for the NLPN in WDM systems [13], [14]. Since the NLPN and laser PN can be considered independent, their variances add-up and the system from the transmitter before pulse shaping to the receiver after equalization and before PN compensation can be modeled as…”
Section: Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations